Bunuel received 6 Kudos for post Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x =.

GiverPostDate
nakulmkRe: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x =12-Jan-2017
PasornsRe: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x =26-Nov-2016
brightfuture90Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x =25-Oct-2016
mfp2632Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x =04-Oct-2016
harishbiyani8888Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x =30-Aug-2015
DienekesRe: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x =20-Apr-2014

Page 1 of 1